Methodology for the Design and Establishment of Synthetic Fish Pond Bio Systems and Fish Harvest Optimization Planning - S. A., Odinazoda; M. Kh., Nimatova; Elmurodova, B. (Research Parks Publishers, 2022)
We show that the intensity of microbiological activities in a complex biodynamics of the entire aquatic system is the basis for high fish production, based on the biological basis of mathematical modeling of productive fish pond ecosystems.